NOGAPS-ALPHA: A Prototype High-Altitude Global NWP Model - Eckermann, Stephen D.; McCormack, John P.; Coy, Lawrence; Allen, Douglas; Hogan, Tim; Kim, Young-Joon (2004)
The Navy Operational Global Atmospheric Prediction System (NOGAPS) is the Department of Defense's (DoD's) high-resolution global numerical weather prediction (NWP) system. Its development and operation is a joint activity of the Naval Research Laboratory (NRL) and the Navy's Fleet Numerical Meteorology and Oceanography Center (FNMOC). NOGAPS is a complete operational forecasting system that includes data quality control, tropical cyclone bogusing, operational data assimilation, balanced initialization, and a global forecast model. Operational NOGAPS forecasts currently consist of high-resolution T239L30 six-day forecasts every 6 hours and once-a-day extended ten-day guidance using the FNMOC ensemble (T119L24). These forecasts are distributed to numerous defense and civilian users, and are used as input for numerous DoD environmental and application systems. Examples include: the Navy's Coupled Ocean-Atmosphere Mesoscale Prediction System (COAMPSTM); FNMOC's ocean wave, sea ice, ocean thermodynamics, and tropical cyclone models; aircraft and ship-routing programs. Presented at the Symposium on the 50th Anniversary of Operational Numerical Weather Prediction, held in College Park, MD, on 14-17 Jun 2004. The original document contains color images.